Profiles of met and unmet care needs in the oldest-old primary care patients with depression - results of the AgeMooDe study - Kraake, Sophia; Pabst, Alexander; Wiese, Birgitt; Moor, Lilia; König, Hans-Helmut; Hajek, André; Kaduszkiewicz, Hanna; Scherer, Martin; Stark, Anne; Wagner, Michael; Maier, Wolfgang; Werle, Jochen; et al. (Journal of affective disorders, 2024)
Background - Unmet care needs have been associated with an increased risk of depression in old age. Currently, the identification of profiles of met and unmet care needs associated with depressive symptoms is pending. Therefore, this exploratory study aimed to identify profiles of care needs and analyze associated factors in oldest-old patients with and without depression. - Methods - The sample of 1092 GP patients aged 75+ years is based on the multicenter study “Late-life depression in primary care: needs, health care utilization and costs (AgeMooDe)”. Depression (i.e. clinically meaningful depressive symptoms) was determined using the Geriatric Depression Scale (GDS) (cutoff score ≥ 4). Needs of patients were assessed using the Camberwell Assessment of Need for the Elderly (CANE). Associated sociodemographic and clinical factors were examined, and latent class analysis identified the need profiles. - Results - The main result of the study indicates three need profiles: ‘no needs’, ‘met physical needs’, and ‘unmet social needs’. Members of the ‘met physical needs’ (OR = 3.5, 95 %-CI: 2.5-4.9) and ‘unmet social needs’ (OR = 17.4, 95 %-CI: 7.7-39.7) profiles were significantly more likely to have depression compared to members of the ‘no needs’ profile. - Limitations - Based on the cross-sectional design, no conclusions can be drawn about the causality or direction of the relationships between the variables. - Conclusions - The study results provide important insights for the establishment of needs-based interventions for GPs. Particular attention should be paid to the presence of unmet social needs in the oldest-old GP patients with underlying depressive symptoms.